Basic symptom-modifying delayed-action drugs in therapy of osteoporosis - Vladimir Vasil'evich Badokin; Vladimir Vasilievich Badokin (Современная ревматология, 2011)
Glucosamine sulfate, or hydrochloride, and chondroitin sulfate are natural components of cartilaginous intercellular substance. In osteoarthrosis (OA), they exert a pronounced symptom-modifying effect and, when used long, they can also inhibit the X-ray progression of OA. The combination drugs that comprise glucosamine and chondroitin have some advantage over each component. These agents include teraflex. The efficacy of these pharmacological agents seems to be associated with their anti-inflammatory properties rather than with the stimulated synthesis of cartilaginous matrix.